Perancangan Galeri Seni Lukis Ivan Hariyanto di Surabaya - Vania Santoso (Intra, 2014)
The making of this essay is about “Designing Ivan Hariyanto’s  paintings gallery in Surabaya” and its purpose is to be a vessel to hold and support Ivan Hariyanto’s artworks. Afterall, Surabaya needs a permanent gallery to spesifically display the artwork from an artist so that visitors from local and abroad can visit and enjoy those paintings, without having to wait for such events.